IMPLEMENTASI LESSON STUDY DALAM MENINGKATKAN MUTU PEMBELAJARAN BAHASA INGGRIS DI SMK BINA INFORMATIKA KOTA TERNATE - Samsudin Hi Adam; Silvani Umar Ali (Jurnal Bilingual, 2022)
Today’s learning activities are still dominated by the teachers and it makes the students’ involvement in the learning process is still very low. Lesson study is one of the efforts to improve the process and learning outcomes carried out collaboratively and sustainably by a group of teachers. This type of research is a lesson study-based Classroom Action Research. It is carried out for three months, starting from August to October 2021. The subjects of this research are 4 English teachers at SMK Bina Informatika Kota Ternate and 30 students in class XI in the 2021/2022 academic year. Data collection technique used is observation. The result indicates the implementation of lesson study has a positive impact on improving the quality of English learning at SMK Bina Informatika Kota Ternate. There is an increase in students’ activity in learning from cycle I to cycle II on the aspects of students' ability to communicate (expressing opinions or asking questions), students' ability to interact and participate in discussions, students' ability to complete tasks given by the teacher, students' ability to present the results of discussions, and the ability of students to respond to the results of other group discussions.